1993
DOI: 10.1117/12.145478
|View full text |Cite
|
Sign up to set email alerts
|

<title>Thermally induced stresses and electromigration failure</title>

Abstract: Attempts to improve the reliability of narrow passivated Al/Cu conductors as defmed by the performance in an accelerated electromigration test are reviewed. The results are explained in terms of the effect of thermally induced stress and stress voiding on electromigration lifetime. Other processing variations which produced small or inconsequential changes are also discussed. In addition, it was observed that electromigration perfonnance in samples susceptible to stress voiding was degraded as a function of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…One therefore expects an improvement in EM lifetime by lowering the processing temperature. In a subsequent work [5], Lloyd and co-workers studied interconnect EM performance for different lots with different processing temperatures, and they found approximately five times improvement in EM life-time by reducing dielectric deposition temperature from 390 o C to 325 o C on the interconnect lines.…”
Section: Introductionmentioning
confidence: 99%
“…One therefore expects an improvement in EM lifetime by lowering the processing temperature. In a subsequent work [5], Lloyd and co-workers studied interconnect EM performance for different lots with different processing temperatures, and they found approximately five times improvement in EM life-time by reducing dielectric deposition temperature from 390 o C to 325 o C on the interconnect lines.…”
Section: Introductionmentioning
confidence: 99%
“…Due to tensile stress remaining in the metallization at EM test condition, EM lifetime improvement can be expected by lowering processing temperature. It is found that EM lifetime in interconnect with different porcessing temperature can be approximately five times improvement by reduction of depostion temperature from 390 0 C to 325 0 C in interconnect lines [49]. This great improvement in EM performance is noticed due to the reduction of tensile stress gradient.…”
Section: Thermo-mechanical Stress Gradient Induced Migration(sm)mentioning
confidence: 92%
“…The non-uniform thermal distribution in the test structure induces a thermo-mechanical stress gradient when it is subjected to raised temperature in EM test conditions. It has been reported that the presence of this stress significantly shortens the EM lifetime [39,40].…”
Section: Theoretical Description and Modeling Physics Of Em In Modernmentioning
confidence: 99%